2020
DOI: 10.1111/his.14186
|View full text |Cite
|
Sign up to set email alerts
|

Undifferentiated endometrial carcinoma arising in the background of high‐grade endometrial carcinoma – Expanding the definition of dedifferentiated endometrial carcinoma

Abstract: Undifferentiated endometrial carcinoma arising in the background of high-grade endometrial carcinoma-Expanding the definition of dedifferentiated endometrial carcinoma Dedifferentiated endometrial adenocarcinoma (DEC) is defined by the coexistence of undifferentiated carcinoma with low-grade (FIGO grade 1 or 2) endometrioid carcinoma. Few cases of DEC arising in the background of high-grade carcinoma (DEC-HG) have been reported, however, this phenomenon is poorly characterized. In this study we describe the mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 26 publications
2
29
0
Order By: Relevance
“…In fact, UEC may show epithelioid, spindled, rhabdoid, or bizarre giant cells, with sometimes myxoid stroma [ 49 ]. The differentiated component of DEC may be high-grade EEC or even SEC [ 50 ]. UEC/DEC might be confused with high-grade EEC, SEC with solid growth pattern, NEEC, carcinosarcoma, or sarcomas, and is probably underrecognized in the common practice [ 51 ].…”
Section: Undifferentiated/dedifferentiated Carcinoma (Uec/dec)mentioning
confidence: 99%
“…In fact, UEC may show epithelioid, spindled, rhabdoid, or bizarre giant cells, with sometimes myxoid stroma [ 49 ]. The differentiated component of DEC may be high-grade EEC or even SEC [ 50 ]. UEC/DEC might be confused with high-grade EEC, SEC with solid growth pattern, NEEC, carcinosarcoma, or sarcomas, and is probably underrecognized in the common practice [ 51 ].…”
Section: Undifferentiated/dedifferentiated Carcinoma (Uec/dec)mentioning
confidence: 99%
“…Dedifferentiated/undifferentiated endometrial carcinoma (DDEC/UEC) is defined in the 2020 World Health Organization (WHO) classification as a malignant epithelial neoplasm with no overt cell lineage differentiation [1]. In the case of dedifferentiated carcinoma, the undifferentiated carcinoma occurs in combination with a clonally related typically International Federation of Gynecology and Obstetrics (FIGO) grade 1 or 2 endometrioid‐type carcinoma [2,3], though the association with high‐grade endometrioid‐type carcinoma also occurs, albeit less commonly [4]. Studies that employed centralized pathology review using strict histologic criteria have demonstrated an aggressive clinical behavior for DDEC/UEC, with significantly worse outcome than International Federation of Gynecology and Obstetrics (FIGO) grade 3 endometrioid carcinoma [2,5–7].…”
Section: Introductionmentioning
confidence: 99%
“…Recent immunochemistry stain findings of the above markers are listed in Table 1 . SWI/SNF complex deficiency ranged from 20.0 to 69.4%, and MMR deficiency (MMRd) ranged from 46.2 to 73.3% across different studies [ 8 , 11 , 18 , 19 , 20 , 21 ].…”
Section: Histological Diagnosis Immunohistochemistry and Genetic Alte...mentioning
confidence: 99%
“…Due to the rarity of UDEC, there was little experience with novel treatment in case series. Real-world experience was limited to conventional chemotherapy and/or radiotherapy [ 49 , 50 ], as listed in Table 2 [ 11 , 21 , 45 , 49 , 50 , 51 ]. According to most clinical guidelines [ 52 , 53 ], comprehensive staging surgery should be performed in operable cases, including total hysterectomy with bilateral salpingo-oophorectomy, systematic lymphadenectomy, and infracolic omentectomy [ 53 ].…”
Section: Treatment and Prognosismentioning
confidence: 99%
See 1 more Smart Citation